2010
DOI: 10.1016/j.biortech.2009.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory scale evaluation of volatile organic compound emissions as indication of swine carcass degradation inside biosecure composting units

Abstract: Biosecure livestock mortality composting systems have been used to dispose of diseased livestock mortalities. In those types of system, visual inspection of carcass degradation is not possible and monitoring VOCs (volatile organic compounds) released by carcasses is a new approach to assess progress of the composting process. In this study, field-scale livestock mortality composting systems were simulated and a laboratory scale composting system with aerobic and anaerobic test units was designed to collect VOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 26 publications
(34 reference statements)
5
28
0
Order By: Relevance
“…The chemical composition of the pine shavings used in this study suggests a possible explanation. Work by Akdeniz et al (2010a) on VOCs released during composting reported that several terpenes (e.g., camphene, limonene, β -pinene, β -phellandrene) were detected in mortality compost that employed pine shavings. These compounds, which have antimicrobial properties (Dermirci et al, 2007, Imelouane et al, 2009Leite et al, 2007), may have been made more available by wetting the shavings, thereby suppressing microbial activity and heat production.…”
Section: Internal Temperature (Field Trials)mentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of the pine shavings used in this study suggests a possible explanation. Work by Akdeniz et al (2010a) on VOCs released during composting reported that several terpenes (e.g., camphene, limonene, β -pinene, β -phellandrene) were detected in mortality compost that employed pine shavings. These compounds, which have antimicrobial properties (Dermirci et al, 2007, Imelouane et al, 2009Leite et al, 2007), may have been made more available by wetting the shavings, thereby suppressing microbial activity and heat production.…”
Section: Internal Temperature (Field Trials)mentioning
confidence: 99%
“…Results of the VOC study are reported in papers by Akdeniz et al (2010aAkdeniz et al ( , 2010bAkdeniz et al ( , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of odorant VOCs in the standard generated gases were calculated as a ratio of the standard mass injected for each compound and the airflow ( Table 2). The resulting concentrations ranged from 4.32 to 888 ppb, i.e., they were within the range of concentrations measured inside livestock barns [37]. The photocatalysis treatment of the gaseous odorant VOCs took place in a 200-mL flow-through UV reaction chamber in a standard gas generation (SGG) system ( Figure 1, Figure S1).…”
Section: Standard Gas Generation and Uv Treatment Systemmentioning
confidence: 99%
“…The selection of target odorants was based on the reported chemical emissions from typical swine barns [37]. A special setup for generating a dynamic (moving) gas mixture was designed, assembled, and tested, using the procedure described by Koziel et al [38] and by Akdeniz et al [39].…”
Section: Standard Gas Generation and Uv Treatment Systemmentioning
confidence: 99%
“…Feedstocks are considered the most important factor in determining what particular intermediate and potentially compounds develop Büyüksönmez et al, 2012). Additional managing factors such as temperature, O 2 levels, humidity, pH and duration of composting are also of significance (Akdeniz et al, 2010;Blazy et al, 2014;Büyüksönmez and Evans, 2007;Delgado-Rodríguez et al, 2012b;Romain et al, 2005).…”
Section: Introductionmentioning
confidence: 99%